The spatial spillover effect and mediating effect of green credit on agricultural carbon emissions: Evidence from China - Qin, Lingui; Liu, Songqi; Hou, Yao; Zhang, Yan; Wu, Dongli; Yan, Dabo (Frontiers in Earth Science, 2023)
Agriculture has become a main source of greenhouse gas emissions globally, so limiting agricultural carbon emissions is an important part of achieving carbon neutrality in China. The reduction of agricultural carbon emissions needs the support of green credit. This paper explores the spatial effect and mechanism of green credit on agricultural carbon emissions. Specifically, based on panel data of 30 Chinese provinces from 2009 to 2019, the relationship between green credit and agricultural carbon emissions is empirically analyzed using spatial econometric and mediating effect models. The results show that green credit has a significant inhibitory effect on agricultural carbon emissions. Meanwhile, green credit can also limit agricultural carbon emissions in surrounding areas through spatial spillover effects. Moreover, the study reveals that green credit can indirectly suppress agricultural carbon emissions by promoting agricultural green technology innovation. Based on the above conclusions, this paper puts forward policy recommendations for the development of green credit and the reduction of agricultural carbon emissions.